Foundations of Modern Science: Ancient Greek Rationality and Epistemic Transformation - Hidayati, Yusranida; Salminawati, Salminawati (Universitas Islam Negeri Sunan Ampel Surabaya, 2025)
This study examines the transformation of philosophical and scientific thought in Ancient Greece. The academic concern driving this research is the limited understanding of how Greek society shifted from myth-based beliefs to a rational mindset that gave rise to philosophy and science. The study employs a qualitative method using a library research approach and descriptive-analytical analysis. The findings reveal that rational thought in Ancient Greece laid the foundation for modern scientific methods through the contributions of figures such as Thales, Heraclitus, Democritus, Socrates, Plato, and Aristotle. They developed rational approaches to nature, ethics, logic, and epistemology. The study also finds that this intellectual shift was influenced by the socio-political dynamics of Ancient Greece, which encouraged the pursuit of knowledge more systematically and objectively.